Rapid pleural effusion after discontinuation of lenvatinib in a patient with pleural metastasis from thyroid cancer. (18th March 2019) - Uchida, Taisuke; Yamaguchi, Hideki; Nagamine, Kazuhiro; Yonekawa, Tadato; Nakamura, Eriko; Shibata, Nobuhiro; Kawano, Fumiaki; Asada, Yujiro; Nakazato, Masamitsu
Summary: We report a case of rapid pleural effusion after discontinuation of lenvatinib. A 73-year-old woman was diagnosed with poorly differentiated thyroid cancer with right pleural metastasis. Weekly paclitaxel treatment was performed for 18 weeks, but it was not effective. Oral administration of lenvatinib, a multi-target tyrosine kinase inhibitor, reduced the size of cervical and thoracic tumors and lowered serum thyroglobulin levels. Lenvatinib was discontinued on day 28 because of Grade 2 thrombocytopenia and Grade 3 petechiae. Seven days after discontinuation of lenvatinib, the patient was hospitalized because of dyspnea and right pleural effusion. Pleural effusion rapidly improved with drainage and re-initiation of lenvatinib and did not recur. Anorexia caused by lenvatinib led to undernutrition, which resulted in death 13 months after initiation of lenvatinib. Autopsy revealed extensive necrosis with primary and metastatic lesions, suggesting that the patient responded to lenvatinib. Physicians should be aware of the possibility of flare-up in patients with thyroid cancer treated with lenvatinib. Learning points: Autopsy findings revealed that lenvatinib was efficacious in treating poorly differentiated thyroid cancer without primary lesion resection. Flare-up phenomenon may occur in thyroid cancer treated with lenvatinib. Attention should be paid to flare-up phenomenon within a few days of discontinuing lenvatinib.